2021
DOI: 10.1111/jcmm.16096
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long non‐coding RNA MEG3 silencing and microRNA‐214 restoration elevate osteoprotegerin expression to ameliorate osteoporosis by limiting TXNIP

Abstract: Studies have shown that long non‐coding RNA (lncRNA) MEG3 plays a key role in osteoporosis (OP), but its regulatory mechanism is somewhat incompletely clear. Here, we intend to probe into the mechanism of MEG3 on OP development by modulating microRNA‐214 (miR‐214) and thioredoxin‐interacting protein (TXNIP). Rat models of OP were established. MEG3, miR‐214 and TXNIP mRNA expression in rat femoral tissues were detected, along with TXNIP, OPG and RANKL protein expression. BMD, BV/TV, Tb.N and Tb.Th in tissue sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The zebrafish larvae at the age of 10 dpf were washed with ultrapure water for five times and then treated with 70% HNO 3 . After that, the samples were placed in microwave oven for 4 h (Yang et al., 2021). The contents of Ca, P, K, Mg, Zn, and Fe in zebrafish larvae were determined by ICP/MS (Agilent, Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The zebrafish larvae at the age of 10 dpf were washed with ultrapure water for five times and then treated with 70% HNO 3 . After that, the samples were placed in microwave oven for 4 h (Yang et al., 2021). The contents of Ca, P, K, Mg, Zn, and Fe in zebrafish larvae were determined by ICP/MS (Agilent, Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The long non-coding RNAs MEG3 and TXNIP are significantly upregulated in OP rats, whereas microRNA (miRNA-214) expression is downregulated. Dual-luciferase reporter gene detection results have confirmed that TXNIP is the downstream target gene of miRNA-214, and MEG3 silencing and miRNA-214 overexpression promote OB proliferation and differentiation by downregulating TXNIP and increasing osteoprotegerin (OPG) expression ( 87 ).…”
Section: Mechanisms Underlying Txnip Involvement In Bone Metabolismmentioning
confidence: 99%
“…Furthermore, they identified that lncRNA LOC100506178 overexpression in BMSCs and transplantation of the same in nude mice reverses the inhibitory effect of miR-214-5p and promoted ectopic bone formation in vivo (Li et al, 2020). While miR-214 was often reported to negatively regulate osteoblast differentiation, Yang et al, (2021) identified that miR-214 could promote osteoblast differentiation by targeting thioredoxin-interacting protein (TXNIP). TXNIP is responsible for bone loss during osteoporosis, hence using a rat osteoporosis model, they found that lncRNA MEG3, which sponges miR-214, was upregulated in the osteoporosis condition.…”
Section: Long Non-coding Rnas Targeting Mir-214mentioning
confidence: 99%